Reasons correlated with omission of nursing care* - Oliveira, Maria Clara Nascimento; Leite, Hillda Dandara Carvalho Santos; Lopes, Vanessa Caminha Aguiar; Cruz, João Victor Oliveira Matos; Vasconcelos, Claudia Daniella Avelino; Nogueira, Lídya Tolstenko (Revista da Escola de Enfermagem da USP, 2022)
Objective: To evaluate the reasons correlated with the omission of nursing care in a university hospital. Method: Analytical cross-sectional design, developed in a university hospital in Northeast Brazil, from January to February 2020. The study population consisted of nurses and nursing technicians who worked in direct patient care. The Brazilian version of the Missed Nursing Care Survey was applied in a convenience sample consisting of 227 participants (79 nurses and 148 nursing technicians). Univariate and bivariate statistics were calculated in the software Statistical Package for Social Science, version 26.0. Results: The most omitted nursing care was walking three times a day or as prescribed (70.9%). The most prevalent reason was an unexpected increase in the volume and/or severity of patients in the unit (93.0%). Positive, albeit weak, correlations were found between overall care omission, as well as omissions by priority level, and reasons for omission given by nurses and nursing technicians (p < 0.05). Conclusion: The study showed that the omission of nursing care covered all five dimensions of the instrument, mainly correlated with labor and material resources.